Continental residual topography extracted from global analysis of crustal structure - Stephenson, SN; Hoggard, MJ; Holdt, MC; White, N (American Geophysical Union, 2024)
Continental topography is dominantly controlled by a combination of crustal thickness and density variations. Nevertheless, it is clear that some additional topographic component is supported by the buoyancy structure of the underlying lithospheric and convecting mantle. Isolating these secondary sources is not straightforward, but provides valuable information about mantle dynamics. Here, we estimate and correct for the component of topographic elevation that is crustally supported to obtain residual topographic anomalies for the major continents, excluding Antarctica. Crustal thickness variations are identified by assembling a global inventory of 26,725 continental crustal thickness estimates from local seismological data sets (e.g., wide-angle/refraction surveys, calibrated reflection profiles, receiver functions). In order to convert crustal seismic velocity into density, we develop a parametrization that is based upon a database of 1,136 laboratory measurements of seismic velocity as a function of density and pressure. In this way, 4,120 new measurements of continental residual topography are obtained. Observed residual topography mostly varies between ±1 and 2 km on wavelengths of 1,000–5,000 km. Our results are generally consistent with the pattern of residual depth anomalies observed throughout the oceanic realm, with long-wavelength free-air gravity anomalies, and with the distribution of upper mantle seismic velocity anomalies. They are also corroborated by spot measurements of emergent marine strata and by the global distribution of intraplate magmatism that is younger than 10 Ma. We infer that a significant component of residual topography is generated and maintained by a combination of lithospheric thickness variation and sub-plate mantle convection. Lithospheric composition could play an important secondary role, especially within cratonic regions.